Europeanisation of social partnership in EU-acceding countries - Elena A. Iankova (Journal for East European Management Studies, 2007)
With the advancement of the eastern enlargement of the EU, some advocates of the European social model saw enlargement as the Trojan horse against Europeanization, for the Americanization of Europe. In response, the EU recommended the strengthening of social partnership among business, labor and the state in candidate countries. This paper reveals four major venues for change: (1) emphasis on a new philosophy of social dialogue as social governance; (2) broadening the scope of participants in social dialogue; (3) development of autonomous and multi-level social dialogue among the organizations of employees and employers; and (4) capacity building for participation of the social partners in EU-level social dialogue. – – Mit der voranschreitenden Ost-Erweiterung der EU sahen einige Verfechter des europäischen Sozialmodels die europäischen Erweiterung als 'Trojanisches Pferd' gegen die Europäisierung und für die Amerikanisierung Europas. Als Antwort empfahlen die EU die Stärkung der sozialen Partnerschaft zwischen den Betrieben, den Arbeitskräften und dem Staat in den Kandidatenländern. Dieser Beitrag zeigt vier bedeutende Arten von Veränderungen: (1) die Betonung einer neuen Philosophie des sozialen Dialoges als soziale Governance; (2) die Erweiterung der Teilnehmer im sozialem Dialog; (3) die Entwicklung von autonomen und mehrstufigen Sozialen Dialogen zwischen den Organisationen von Arbeitsnehmern und Arbeitsgebern; und (4) die Entwicklung der Aufnahmefähigkeit für die Beteiligung der Sozialpartner am Sozialen Dialog auf Ebene der EU.
Keywords: 650; social partnership; social dialogue; Eastern enlargement of the European Union